Development of an Android-Based Educational Game for Early Childhood Mathematics Learning Using Fisher–Yates Shuffle - Egi Bahari Dwi Fraska; Umi Chotijah; Putri Aisyiyah Rakhma Devi (P3M Politeknik Negeri Bengkalis, 2026)
This study aims to develop an Android-based educational game to support early childhood mathematics learning through an interactive approach. The game implements the Fisher–Yates shuffle algorithm to randomize question sequences and object positions, with the goal of reducing repetition and increasing gameplay variation. The development process follows the Software Development Life Cycle (SDLC), including requirements analysis, planning, design, development, and testing. System evaluation is conducted using black-box and white-box testing to assess functionality and algorithm implementation. The results show that all system features operate as expected, achieving a 100% success rate with no identified errors. In addition, the Fisher–Yates shuffle algorithm produces unique random sequences across all trials, indicating consistent randomization performance. These findings demonstrate that the developed application functions reliably and has potential as a supporting tool for early childhood mathematics learning.